Implementation of Science Module Integrated with Google Colaboratory to Improve Students’ Computational Thinking Skill. Is it Effective? - Ningsih, Silvi Putri Ayu; Ridlo, Zainur Rasyid; Rusdianto, Rusdianto; Dewi, Jiniari Apriska (Pedagogi: Jurnal Ilmu Pendidikan, 2024)
Computational thinking skills are one of the supporters of the achievement of 21st century skills. Computational thinking is recognised as the third pillar of science, along with theory and experimentation. This study aims to improve students’ computational thinking skill through implementation science module integrated with Google Colaboratory. Computational thinking skills in students can be improved through learning programming. Students must be guided to connect concepts and activities from students by creating computer programming. This research uses one group pretest-posttest, then the result will be analyzed using N-gain and paired sample test. The object of this research is 36 students in junior high school level. The result of this study shows that the mean of the pre-test score is 27,25 and the mean of the post-test score being 62,36 with the N-gain score is 0,48 in the moderate category. Results of paired sample test show a Sig. (2-tailed) of 0.000, which is smaller than the threshold of 0.05. This result shows that the implementation of the learning module had a significant positive effect on improving computational thinking skills.